Self-Isolated Surface-Mountable MIMO Antenna for FR1 Band Communications - Arpita Patel; Abdulkarem H. M. Almawgani; Trushit Upadhyaya; Vishal Sorathia; Vipul Dabhi; Seif Shebl (International Journal of Antennas and Propagation)
The proposed surface-mountable self-isolated MIMO antenna covers n78 and n79 5G frequency bands. The presented design has two semicircular slots with engineered geometry to get the desired frequency spectrum. Antenna presents the bandwidth in the order of 8.77% and 2.81% at frequency resonance of 3.42 GHz and 4.98 GHz, respectively, covering FR1 5G and WLAN applications. The design presents an acceptable gain of 2.95 dBi and 2.42 dBi. The elements of MIMO antennas are kept an adequate distance apart to achieve self-isolation in order of 19 dB. It aids further in achieving optimal MIMO diversity parameters. The 2D electrical size of the presented self-isolated planar antenna is 0.97λ × 0.65λ at the lowest resonance. The MIMO antenna parameters were examined for the stated antenna design. The optimal envelope correlation coefficient (ECC) is near to 0.02, channel capacity loss (CCL) is around 0.2 bits/sec/Hz, directivity gain (DG) is around 9.98 dB, and the MEG ratios are near to unity. The computed performance of the resonator is validated through fabrication and experimentally tested using VNA 9912A in an anechoic chamber environment.